SUNDANESE STUDENTS’ PRODUCTION OF ENGLISH DENTAL FRICATIVE CONSONANT SOUNDS - Anggi Kharismayuda Guntari (Universitas Gadjah Mada, 2013)
This research attempts to investigate the production of English dental fricative sounds by Sundanese students of Universitas Gadjah Mada. It aims to investigate the level of acceptability and to find out the possible factors which influence their production of these sounds. 700 sentences containing the four dental fricative consonants were obtained and used as the data of the research. The students’ production of the four consonants was then assessed by a native speaker of English for their acceptability. The results of this research show that the acceptability level as judged by the informant of the students’ production of the dental fricative sounds is low, only 13.80% on average. The highest acceptability is in the sound [f] with 45.56%. The second highest acceptability is in the sound [v] which is scored 5%. It is followed by the sound [θ] which is scored 2.78%, and the sound [ð] with 1.88%. In general, the production of the dental fricative sounds produced by Sundanese students is judged as not clear by the native speaker.